'Unfocused groups': lessons learnt amid remote focus groups in the Philippines. (4th August 2021) - Aligato, Mila F; Endoma, Vivienne; Wachinger, Jonas; Landicho-Guevarra, Jhoys; Bravo, Thea Andrea; Guevarra, Jerric Rhazel; Landicho, Jeniffer; McMahon, Shannon A; Reñosa, Mark Donald C
Abstract : The ongoing COVID-19 pandemic has required tremendous shifts in data collection techniques. While an emerging body of research has described experiences conducting remote interviews, less attention has been paid to focus group discussions (FGDs). Herein, we present experiences conducting remote FGDs (n=9) with healthcare workers and caretakers of small children in the Philippines. We used 'Facebook Messenger Room' (FBMR), the preferred platform of participants. Despite some success, we generally encountered considerable challenges in terms of recruiting, retaining and moderating remote FGDs, particularly among caretakers of small children. Finding a quiet, private place proved unfeasible for many participants, who were juggling family demands in tight, locked down quarters. Connectivity issues and technological missteps compromised the flow of FGDs and minimised the ability to share and compare opinions. For the research team, remote FGDs resulted in a dramatic role shift for notetakers—from being passive observers to active tech supporters, chatbox referees and co-moderators (when audio disruptions occurred). Finally, we note that remote FGDs via FBMR are associated with ethical complexities, particularly as participants often chose to use their personal Facebook accounts, which can compromise anonymity. We developed and continuously refined strategies to mitigate challenges, but ultimately decided to forgo FGDs. We urge fellow researchers with more successful experiences to guide the field in terms of capturing high-quality data that respond to research questions, while also contending with privacy concerns, both in online spaces, as well as physical privacy despite lockdowns in tight quarters.